Migraine and stress: an integrative review - Bezerra, Francimar Nipo; Valença, Marcelo Moraes (Headache Medicine, 2016)
The World Health Organization recognizes the headache as a major cause of disability and primarily responsible for reduced quality of life, especially migraine, whose prevalence changes throughout life and generates economic repercussions. Objective: Identify the contribution of research on the relationship between migraine and stress. Methods: integrative literature review. Were used databases as LILACS, MEDLINE, and the Evidence Portal Cocrhane. The strategies used to survey the items were adapted for each database, being guided by the guiding question and inclusion criteries. The search strategies used were "headache for stress," "migraine with aura and migraine without aura", "migraine with aura and migraine without aura and physiological stress or psychological stress." The inclusion criteries for the selection of the sample were articles published in Portuguese and English, which reflect the theme studied, published and indexed in these databases. Results and Discussion: After analysis of the articles, eight were selected and identified two thematic categories about the relationship between migraine and stress: stress as a triggering factor of migraine and stress triggered by migraine. Conclusion: Independent of the relationship between migraine and stress, highlights the relevance of stress identification and use of coping to prevent illness or worsening of the individual’s health status.